2018
DOI: 10.1590/s0102-865020180030000009
|View full text |Cite
|
Sign up to set email alerts
|

Prospective ultrasonographic study of blood flow and testicular volume in patients submitted to surgical repair of inguinal hernia without using prosthesis

Abstract: Prospective ultrasonographic study of blood flow and testicular volume in patients submitted to surgical repair of inguinal hernia without using prosthesis 1 AbstractPurpose: To evaluate the behavior of arterial circulation and testicular volume in patients submitted to conventional inguinal hernia repair without the use of a synthetic prosthesis to reinforce the posterior wall. Methods: A prospective observational clinical trial was performed on 26 male patients with unilateral inguinal hernia types I and II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The length, width and thickness of the testis were measured, and then its volume was calculated (length × width × thickness in cm × 0.52). 26 The statistical relationship between total testicular volume (TTV) and testosterone concentration was determined in patients from the G4 and G5 groups. TTV means the summed volume of both testes (detorted and the contralateral) or only of the contralateral one in case of orchiectomy.…”
Section: Methodsmentioning
confidence: 84%
“…The length, width and thickness of the testis were measured, and then its volume was calculated (length × width × thickness in cm × 0.52). 26 The statistical relationship between total testicular volume (TTV) and testosterone concentration was determined in patients from the G4 and G5 groups. TTV means the summed volume of both testes (detorted and the contralateral) or only of the contralateral one in case of orchiectomy.…”
Section: Methodsmentioning
confidence: 84%
“…Use non-absorbent threads for fixation, recommend and do simultaneous fixation of the second testis for prophylactic purposes. When examining patients operated on due to inguinal hernia, David and Goldenberg [24] and Stula et al [28] found no significant late abnormalities of PSV, EDV, and RI in the capsular and intratesticular arteries. However, according to Çelebi et al [22] and Palabiyik et al, [26] a statistically significant increase in RI and decrease in EDV in these vessels indicates an early, transient testicular blood supply disorder after hernia surgery associated with vasospasm caused by surgical trauma.…”
Section: All Above Authorsmentioning
confidence: 98%
“…The length, width, and thickness of the testis were measured and its volume was calculated from the ellipsoidal formula: volume = length  width  thickness in cm  0.52. [24] Peak-systolic velocity (PSV) and end-diastolic velocity (EDV) were measured in the capsular and intra-testicular arteries and vascular resistance index (RI) was calculated from equation: RI = (PSV À EDV): PSV  100. [21] For statistical comparisons, the mean testicular volume, PSV, EDV, and RI in each developmental group were calculated.…”
Section: The Follow-up Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations